Redesigning the Post-Pandemic Workplace - Kane, Gerald; Kane, Gerald; Nanda, Rich; Phillips, Anh; Copulsky, Jonathan (MIT Sloan Management Review, 2021)
As organizations plan for ways to bring remote employees back to the workplace, they should take advantage of the opportunity to rethink how and where work is best done, and how to combine the best aspects of remote and colocated work.